Pengaruh Kualitas Pelayanan dan Fasilitas Terhadap Kepuasan Konsumen Pada Mini Market Afif Toserba Di Kecamatan Kibin Serang - Siti Ferliana; Juhandi; Abdul Aziz (Fakultas Ekonomi dan Bisnis Universitas Prima Graha, 2021)
Customer satisfaction is affected by the quality of services and facilities. If the service variable can be improved and the facilities are in accordance with the expectations and demands of customers, a higher impact on customer satisfaction will be obtained. The purpose of this study was to determine whether the quality of service and facilities affect customer satisfaction at the Mini Market Afif Toserba in Kibin District, Serang. This study uses a survey method with a quantitative approach. With a sample of 80 respondents who are customers of Mini Market Afif Toserba. Based on data analysis on the partial significance test of the service quality variable, it shows the value of Sig. 0.000 ttable 1.668 and the facility variable shows the value of Sig. 0.000 ttable 1.668. While the simultaneous significance test shows the value of Sig. 0.000 < 0.05 and Fcount 37.162 > Ftable 2.37. Based on the results of data analysis, it can be concluded that the service quality variable (X1) and the facility variable (X2) have a significant effect on the customer satisfaction variable (Y) partially or simultaneously.